Physicochemical characteristics and textural parameters of restructured pork steaks hydrolysed with bromelain. (1st November 2021) - Saengsuk, Nachomkamon; Laohakunjit, Natta; Sanporkha, Promluck; Kaisangsri, Nattapon; Selamassakul, Orrapun; Ratanakhanokchai, Khanok; Uthairatanakij, Apiradee
Graphical abstract: Highlights: Bromelain treatments (0.05 and 0.1% w/w) increased the tenderness of restructured pork steak. Texture profile parameters decreased upon bromelain treatments. Bromelain treatments enhanced TPS, TCA-soluble peptides and HP contents. SEM and SDS-PAGE demonstrated observable degradation of proteins upon bromelain treatments. Abstract: Enzymatic tenderisation including bromelain enhances underused cuts of meat in emerged restructuring technology. Physicochemical and textural characteristics of restructured pork steak hydrolysed with bromelain for masticatory dysfunction people were evaluated. Restructured pork steak treated with bromelain at 0.05 and 0.1% (w/w) was hydrolysed at 50 °C for 0, 3, 6, 9 and 12 min. The cooking losses of 0.05% (w/w) bromelain for 0, 3 and 6 min were lower than 0.1% (w/w) bromelain samples. The ΔE increased after increasing the enzyme concentration and hydrolysis time. Bromelain-treated samples at higher concentrations showed lower WBSF, KSF and TPA parameters, but cohesiveness of 0.05% (w/w) had higher than 0.1% (w/w) bromelain samples. Total protein, sarcoplasmic protein solubility, TCA-soluble peptide, total collagen and soluble collagen contents were the highest in 0.1% (w/w) bromelain-treated samples for 12 min ( P < 0.05). According to SDS-PAGE and SEM, various proteins in the enzyme-treated samples were degraded.